Gene-Rich Large Deletions Are Overrepresented in POAG Patients of Indian and Caucasian Origins - Kaurani, Lalit (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. Large copy number variations (CNV) can contribute to increased burden for neurodegenerative diseases. In this study, we analyzed the genome-wide burden of large CNVs > 100 kb in primary open angle glaucoma (POAG), a neurodegenerative disease of the eye that is the largest cause of irreversible blindness. METHODS. Genome-wide analysis of CNVs > 100 kb were analyzed in a total of 1720 individuals, including an Indian cohort (347 POAG cases and 345 controls) and a Caucasian cohort (624 cases and 404 controls). All the CNV data were obtained from experiments performed on Illumina 660W-Quad (infinium) arrays. RESULTS. We observed that for both the populations CNVs > 1 Mb was significantly enriched for gene-rich regions unique to the POAG cases (P < 10(−11)). In the Indian cohort CNVs > 1 Mb (39 calls) in patients influenced 125 genes while in controls 31 such CNVs influenced only 5 genes with no overlap. In both cohorts we observed 1.9-fold gene enrichment in patients for deletions compared to duplications, while such a bias was not observed in controls (0.3-fold). Overall duplications > 1 Mb were more than deletions (Del/Dup = 0.82) confirming that the enrichment of gene-rich deletions in patients was associated with the disease. Of the 39 CNVs > 1 Mb from Indian patients, 28 (72%) also were implicated in other neurodegenerative disorders, like autism, schizophrenia, sensorineural hearing loss, and so forth. We found one large duplication encompassing CNTN4 gene in Indian and Caucasian POAG patients that was absent in the controls. CONCLUSIONS. To our knowledge, our study is the first report on large CNV bias for gene-rich regions in glaucomatous neurodegeneration, implicating its impact across populations of contrasting ethnicities. We identified CNTN4 as a novel candidate gene for POAG.